KEMAMPUAN KLASIFIKASI LOGIS ANAK : Studi Tentang Kemampuan Abstraksi dan Inferensi Anak Usia Sekolah Dasar pada Kelompok Budaya Sunda - Nuryani Yogipranata Rustaman, - (1990)
A study on the classificatory ability [arrayed into four kinds of classification i.e. matrices classification (KM), classificatory alternatives (AK), reclassification (KU) and class inclusion (IK)] of 6 to 12 year-old children was conducted. Subjects (N=83) consisted of Sundanese children living in urban and rural areas from 10 locations in West Java. Using clinical method they were asked to classify pictorial cards (man, animals, flowers, vehicles) and geometric shapes in order to find out their ability in abstractions and inferences. Their convergent, alternative, dichotomous and hierarchical thinking; their inclusiveness and quantification; as well as the approximate ages of the formation of each logical classificatory ability and their type of inferences have been analyzed. In-depth study against 9 children showing specific cases from previous results was carried out to investigate factors influencing their ability.It was found that the subjects had high abstraction on inclusiveness (IK: 8 years old) and convergent thinking (KM: 0-9 years old), average hierarchical and dichotomous thinking (KU: 9-10 years old) and low alternative or divergent thinking (AK: undetectable). The most and ear-liest type of inferencing was inductive, then deductive and later the combination of the two types. The sequence of each logical classificatory ability was IK, KM, KU and AK. The sequence of classificatory ability was not only age-related, but also complexity-related. There was a close interaction between inherent and external factors in logical classificatory ability.